PENGARUH KOMPETENSI, GAYA KEPEMIMPINAN PARTISIPATIF DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PESENKOPI DI MALANG - Ema Desia Prajitiasari; Arnis Budi Susanto; Intan Nurul Awwaliyah; Diana Sulianti K. Tobing; Mohamad Satria Abimantara (VALUE: Journal of Business Studies, 2022)
This article aims to analyze the effect of competence, participatory leadership style and organizational culture on employee performance at Pesenkopi in Malang. This study used a sample of 60 respondents who were taken using saturation sampling technique.data were analyzed using multiple linear regression using software version 24. The results showed thatcompetence, participatory leadership style and organizational culture had a significant positive effect on the performance of Pesenkopi employees in Malang.